2020
DOI: 10.1139/cjfas-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural adjustment of fish to temporal variation in fishing pressure affects catchability: an experiment with angled trout

Abstract: In passive fisheries, such as angling, the fishing success depends on the ultimate decision of a fish to ingest the bait, based on an individual’s internal state, previous experience, and threat perception. Fish surviving capture by anglers are known to be less vulnerable, and catch rates usually quickly decline with increasing fishing effort. Previous theoretical models have thus suggested fishing closures as a means to recover responsiveness of fish to angling gear and maintain catch rates, yet empirical sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…It will be an important question for future studies whether a single social hooking event would be remembered for longer time frames or get lost through fading memory over time. As recurrent negative stimuli may be important when shaping the learning response in fish with direct experience (Coble et al 1985), repeated angling exposure (Koeck et al 2020), an increase in magnitude of the stressor (Barton 2002), and the social learning mechanism (Brown and Laland 2003;Rendell et al 2011) might affect whether or not decreased vulnerability will be retained in the social individuals for a longer time period.…”
Section: Coefficientsmentioning
confidence: 99%
See 2 more Smart Citations
“…It will be an important question for future studies whether a single social hooking event would be remembered for longer time frames or get lost through fading memory over time. As recurrent negative stimuli may be important when shaping the learning response in fish with direct experience (Coble et al 1985), repeated angling exposure (Koeck et al 2020), an increase in magnitude of the stressor (Barton 2002), and the social learning mechanism (Brown and Laland 2003;Rendell et al 2011) might affect whether or not decreased vulnerability will be retained in the social individuals for a longer time period.…”
Section: Coefficientsmentioning
confidence: 99%
“…Catch and release has sublethal effects on fish (e.g., inducing hooking-related injuries and physiological stress responses; Pankhurst and Dedual 1994;Meka and McCormick 2005), which can lead to behavioral changes in released fish, such as decreased activity (Schreer et al 2005;Halttunen et al 2010;Klefoth et al 2011) and altered feeding (Stålhammar et al 2012). The experience of being captured and released can also induce hook avoidance learning, which has been documented in as diverse species as Common Carp (Beukema 1970a;Raat 1985;Klefoth et al 2013), Northern Pike (Beukema 1970b;Arlinghaus et al 2017aArlinghaus et al , 2017b, Largemouth Bass (Anderson and Heman 1969;Wegener et al 2018;Louison et al 2019b), and Rainbow Trout Oncorhynchus mykiss (Askey et al 2006;Lovén Wallerius et al 2019;Koeck et al 2020). Hook avoidance learning decreases overall angling vulnerability and can penalize future catch rates (Beukema 1970a(Beukema , 1970bvan Poorten and Post 2005;Klefoth et al 2013;Monk and Arlinghaus 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to potential lethal impacts, C&R can produce multiple sublethal stress responses, including elevated plasma concentrations of cortisol (Meka & McCormick, ; Pankhurst & Dedual, ), increased cardiac activity (i.e., heart rate, cardiac output and stroke volume) (Anderson et al, ; Cooke, Philipp, Dunmall, & Schreer, ; Cooke, Schreer, Dunmall, & Philipp, ) and behavioural changes for a certain period following the release (Klefoth, Kobler, & Arlinghaus, ; ). As a consequence, individual fish can develop hook avoidance behaviour through private experiences of hooking (Askey, Richards, Post, & Parkinson, ; Beukema, , ; Klefoth, Pieterek, & Arlinghaus, ; van Poorten & Post, ; Raat, ; Young & Hayes, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, individual fish can develop hook avoidance behaviour through private experiences of hooking (Askey, Richards, Post, & Parkinson, ; Beukema, , ; Klefoth, Pieterek, & Arlinghaus, ; van Poorten & Post, ; Raat, ; Young & Hayes, ). In addition, population‐level catchability has been found to be affected by angling effort without necessarily all fish being hooked and released (e.g., ; Kuparinen, Klefoth, & Arlinghaus, ; Alós, Palmer, Trías, Díaz‐Gil, & Arlinghaus, ; Wegener, Schramm, Neal, & Gerard, ). Experimental pond studies with carp, Cyprinus carpio L. (Beukema, ; Klefoth et al, ; Raat, ), and pike, Esox Lucius L. (Beukema, ), have suggested that social learning might play a role in observed decreases of overall catchability.…”
Section: Introductionmentioning
confidence: 99%